Inclusivity In Music Concerts: Case Study Of Coldplay Music Concerts In Jakarta And Singapore - Litani, Aymi; Rahmanita, Myrza; Oktadiana, Hera; Sulartiningrum, Sri (Ann Publisher, 2025)
Background. Inclusive tourism emphasizes equal access for all individuals, including people with disabilities, to participate in tourism activities, including international music concerts fully. Aims. This study aims to analyze the role of promoters in implementing inclusivity in organizing Coldplay concerts in Jakarta and Singapore. Methods. The study was conducted at Gelora Bung Karno Stadium and the National Stadium between November 2023 and January 2024, using a qualitative approach through observation and interviews. It was analyzed using the SWOT method to identify strengths, weaknesses, opportunities, and threats. The results show that PK Entertainment in Jakarta and Live Nation Singapore both play strategic roles in translating Coldplay's commitment to inclusivity into the concert experience. Conclusion. Jakarta has the strength of a large fan base and promoter credibility. Still, it faces infrastructure limitations and low awareness of inclusivity, while Singapore excels in infrastructure readiness and inclusive service standards despite facing high operational costs and public expectations. Implementation. These findings emphasize the importance of collaboration between promoters, venue managers, the government, and inclusive communities to realize music concerts as a form of sustainable inclusive tourism.